Differential Roles of Glycogen Synthase Kinase 3 Subtypes Alpha and Beta in Cortical Development - Ma, Yan-xia; Wang, Xiu-li; Chen, Jian-quan; Li, Bin; Hur, Eun-Mi; Saijilafu (FRONTIERS MEDIA SA, 2017)
Glycogen synthase kinases 3 (GSK3) alpha and beta are expressed in the nervous system, and disruption of GSK3 signaling has been implicated in a wide range of neurodevelopmental and psychiatric disorders. Although several studies have established a role of GSK3 signaling in the nervous system, much less is known about isoform-specific functions. Here, we have examined the role of GSK3 alpha and GSK3 beta in the developing neocortex by performing in utero electroporation with specific small interfering RNAs targeting each isoform. We found that depletion of either GSK3 alpha or GSK3 beta commonly promoted the proliferation of neural progenitor cells in the ventricular zone, but at later stages, knocking down of each isoform resulted in distinct outcomes. In particular, the transformation of radial progenitors to intermediate progenitor cells was promoted in GSK3 alpha-depleted cells, but markedly prevented in GSK3 beta-depleted cells. Moreover, knocking down of GSK3 beta but not GSK3 alpha prevented the generation of upper-layer Cux1(+) neurons. Consistent with the distinct outcomes, protein levels of c-Myc and beta-catenin, well-known substrates of GSK3, were differentially affected by depletion of GSK3 alpha and GSK3 beta. Together, these results suggest that GSK3 alpha and GSK3 beta might play distinct roles in the genesis and differentiation of neuronal lineage cells during neocortex development by differential regulation of downstream signaling pathways.
Keywords: NEURONS ARISE; SCHIZOPHRENIA; GSK-3; PHOSPHORYLATION; PROLIFERATION; KINASE-3-BETA; SPECIFICATION; PROGENITORS; EXPRESSION; MUTATIONS